The AD and ELENA orbit, trajectory and intensity measurement systems. (27th July 2017) - Marco-Hernández, R.; Alves, D.; Angoletta, M.E.; Marqversen, O.; Molendijk, J.; Oponowicz, E.; Ruffieux, R.; Sánchez-Quesada, J.; SØby, L.
Abstract: This paper describes the new Antiproton Decelerator (AD) orbit measurement system and the Extra Low ENergy Antiproton ring (ELENA) orbit, trajectory and intensity measurement system. The AD machine at European Organization for Nuclear Research (CERN) is presently being used to decelerate antiprotons from 3.57 GeV/c to 100 MeV/c for matter vs anti-matter comparative studies. The ELENA machine, presently under commissioning, has been designed to provide an extra deceleration stage down to 13.7 MeV/c. The AD orbit system is based on 32 horizontal and 27 vertical electrostatic Beam Position Monitor (BPM) fitted with existing low noise front-end amplifiers while the ELENA system consists of 24 \gls{BPM}s equipped with new low-noise head amplifiers. In both systems the front-end amplifiers generate a difference (delta) and a sum (sigma) signal which are sent to the digital acquisition system, placed tens of meters away from the AD or ELENA rings, where they are digitized and further processed. The beam position is calculated by dividing the difference signal by the sum signal either using directly the raw digitized data for measuring the turn-by-turn trajectory in the ELENA system or after down-mixing the signals to baseband for the orbit measurement in both machines. The digitized sigma signal will be used in the ELENA system to calculate the bunched beam intensity and the Schottky parameters with coasting beam after passing through different signal processing chain. The digital acquisition arrangement for both systems is based on the same hardware, also used in the ELENA Low Level Radio Frequency (LLRF) system, which follows the VME Switched Serial (VXS) enhancement of the Versa Module Eurocard 64x extension (VME64x) standard and includes VITA 57 standard Field Programmable Gate Array Mezzanine Card (FMC). The digital acquisition Field Programmable Gate Array (FPGA) and Digital Signal Processor (DSP) firmware shares many common functionalities with the LLRF system but has been tailored for this measurement application in particular. Specific control and acquisition software has been developed for these systems. Both systems are installed in AD and ELENA. The AD orbit system currently measures the orbit in AD while the ELENA system is being used in the commissioning of the ELENA ring.